Specific olfactory neurons and glomeruli are associated to differences in behavioral responses to pheromone components between two Helicoverpa species - Wu, Han; Xu, Meng; Hou, Chao; Huang, Ling-Qiao; Dong, Jun-Feng; Wang, Chen-Zhu (Frontiers in Behavioral Neuroscience, 2015)
Sex pheromone communication of moths helps to understand the mechanisms underlying reproductive isolation and speciation. Helicoverpa armigera and Helicoverpa assulta use (Z)-11-hexadecenal (Z11-16:Ald) and (Z)-9-hexadecenal (Z9-16:Ald) as pheromone components in reversed ratios, 97:3 and 5:95, respectively. H. armigera also produces trace amount of (Z)-9-tetradecenal (Z9-14:Ald) in the sex pheromone gland, but H. assulta does not. Wind tunnel studies revealed that the addition of small amounts (0.3%) of Z9-14:Ald to the main pheromone blend of H. armigera increased the males’ attraction, but at higher doses (1 %, 10 %) the same compound acted as an inhibitor. In H. assulta, Z9-14:Ald reduced male attraction when presented as 1% to the pheromone blend, but was ineffective at lower concentrations (0.3%). Three types (A, B, and C) of sensilla trichodea in antennae were identified by single sensillum recording, responding to Z11-16:Ald, Z9-14:Ald, and both Z9-16:Ald and Z9-14:Ald, respectively. Calcium imaging in the antennal lobes (ALs) revealed that the input information of the three chemicals was transmitted to three units of the macroglomerular complex (MGC) in ALs in both species: a large glomerulus for the major pheromone components, a small one for the minor pheromone components, and a third one for the behavioral antagonists. The type A and C neurons tuned to Z11-16:Ald and Z9-16:Ald had a reversed target in the MGC between the two species. In H. armigera, low doses (1 µg, 10 µg) of Z9-14:Ald dominantly activated the glomerulus which processes the minor pheromone component, while a higher dose (100µg) also evoked an equal activity in the antagonistic glomerulus. In H. assulta, instead, Z9-14:Ald always strongly activated the antagonistic glomerulus. These results suggest that Z9-14:Ald plays different roles in the sexual communication of two Helicoverpa species through activation of functionally different olfactory pathways.